An analysis of promotional genre in job application letters / Nuruladilah Mohamed ... [et al.] - Mohamed, Nuruladilah; Halim, Nur Syazwani; Husin, Norhayati; Mokhtar, Norashikin (2017)
This paper presents the result of genre analysis on the job application letter. This type of letter is the one that the job applicant writes to the Human Resource (HR) department when applying a position of Senior Executive Officer in several private financial institutions in Malaysia. This study adapts the latest framework of moves and steps by Khan and Tin (2012) and based on the framework, fifteen job application letters written by Malaysian second language (L2) English writers were analysed in terms of the moves and steps and also its communicative purposes. Detailed analysis of the letters was carried out first to analyze moves and steps used to implement promotional genre and the communicative purposes were then identified. The conclusion indicates that this type of analysis provides future researcher with essential information that can be used to develop more suitable move structures and implementation that should be applied by the job applicants. Moreover, the analysis provides future job applicants with information on how to achieve the communicative purposes of their application letter.